UJI AKTIVITAS SEDIAAN SPRAY HAND SANITIZER KOMBINASI EKSTRAK DAUN KEMANGI DAN DAUN JERUK NIPIS SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus aureus - Idham Halil Zakaria; Cecilia Anna Seumahu; Amos Killay (LP4MK STKIP PGRI Lubuklinggau, 2022)
Basil and lime leaf extracts have chemical compounds that function to inhibit the growth of Staphylococcus aureus and total bacteria on the palms of the hands. The purpose of this study was to determine the antibacterial activity of basil and lime leaf extracts against Staphylococcus aureus total bacteria on the palms of the hands. This experimental laboratory research used basil and lime leaves which were extracted using the partial maceration method. The formulation of the hand sanitizer spray combination of basil leaf extract with lime leaves is 1:2, 2:1, and 2:2. The formulation was tested for an antibacterial effect on Staphylococcus aureus and total bacteria on the palms. Data analysis used descriptive quantitative. The results showed that the extracts of basil leaves and lime leaves had an antibacterial activity of Staphylococcus aureus and total bacteria. Formulation 2:2 is the best formulation with bactericidal power of formula is 0 CFU/ml and total bacteria with antiseptic power of formula are 7 CFU. The study concluded that basil and lime leaf extracts were effective in killing Staphylococcus aureus and total bacteria on the palms of the hands.